The treatment analysis of the patients suffering from vaginismus and the correlation with the psychological issues - Kurban, Didem; Eserdag, Suleyman; Yakut, Emrah; Mishra, Prabhu Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: We aimed to present the demographic information, treatment protocol, and results of 482 female patients that presented to our clinic specialized in sexual dysfunction with the complaint of no or only partial sexual intercourse and were diagnosed with primary vaginismus. Methods: The female patients were asked eight questions about demographics; 13 questions about marriage; seven questions about family structure and upbringing; three questions about history of psychiatric diseases and general phobias; and 17 questions about sexual history and previous treatments. The male spouses were asked seven questions concerning age, occupation, educational level, personality, sexual experience, and sexual dysfunction. Results: The median age of the female patients was 28 and their spouses was 29. The mean duration of marriage was 18.2 months. Of the female patients, 65.4% reported that they felt they would have pain during sexual intercourse, 23.6% stated that they really had pain, 74.1% mentioned that they had heard horrifying stories about the first night of marriage in the pre-marital period. Cognitive behavioral therapy was performed alone in 85.7% of the patients, following hymenotomy in 5%, and following hymenectomy in 9.3%. Conclusions: False and exaggerated information about sexuality being embedded in the subconscious of women is very effective in the development of vaginismus. On the other hand, traditional family structure, adolescent traumas, first night stories, and superstitions about sexuality are among the important causes of vaginismus.